Exit City. Volume 1 - London, Mark (Graphic novelist) (Mad Cave Studios, 2025)
In Exit City, there's a thin line between good and evil, and Detectives McCormick and Miller are about to find out the hard way. When they come to the scene of a brutal accident, McCormick and Miller must work together through a web of seedy criminals, genetic experiments, and crooked government officials. But those aren't the only things standing in their way, because McCormick is hiding a secret that would make anyone question his capabilities and their own reality.